Gut microbiota of the threatened takahē: biogeographic patterns and conservation implications - West AG; DeLaunay A; Marsh P; Perry EK; Jolly M; Gartrell BD; Pas A; Digby A; Taylor MW (BioMed Central Ltd, 2022)
BACKGROUND: The Aotearoa New Zealand takahē (Porphyrio hochstetteri), once thought to be extinct, is a nationally threatened flightless rail under intensive conservation management. While there has been previous research into disease-related microbes in takahē, little is known about the microbes present in the gastrointestinal tract. Given the importance of gut-associated microbes to herbivore nutrition and immunity, knowledge of these communities is likely to be of considerable conservation value. Here we examined the gut microbiotas of 57 takahē at eight separate locations across Aotearoa New Zealand. RESULTS: Faecal samples, taken as a proxy for the hindgut bacterial community, were subjected to 16S rRNA gene amplicon sequencing using Illumina MiSeq. Phylogenetic analysis of > 2200 amplicon sequence variants (ASVs) revealed nine main bacterial phyla (Acidobacteriota, Actinobacteriota, Bacteroidota, Campilobacterota, Firmicutes, Fusobacteriota, Planctomycetota, Proteobacteria, and Verrucomicrobiota) that accounted for the majority of sequence reads. Location was a significant effect (p value < 0.001, 9999 permutations) that accounted for 32% of the observed microbiota variation. One ASV, classified as Lactobacillus aviarius, was present in all samples at an average relative abundance of 17% (SD = 23.20). There was strong evidence (p = 0.002) for a difference in the abundance of the genus Lactobacillus between locations. A common commensal bacterium previously described in takahē, Campylobacter spp., was also detected in most faecal samples. CONCLUSIONS: Location plays a pivotal role in the observed variation among takahē gut bacterial communities and is potentially due to factors such as supplemental feeding and medical treatment experienced by birds housed in captivity at one of the eight sampled sites. These data present a first glimpse of the previously unexplored takahē gut microbiota and provide a baseline for future microbiological studies and conservation efforts.
Keywords: Avian; Bird; Conservation; Endangered; Microbiome; Microbiota